Morphometric, Meristic, and Growth Patterns of the Strombus turturella from the Dompak Island Coastal Area, Tanjungpinang Kepulauan Riau - Henny, Henny; Eddiwan, Eddiwan; Efawani, Efawani (Asian Journal of Aquatic Sciences, 2019)
Strombus turturella is a type of gastropods that live in the shallow coastal area of the Dompak Island. A research aims to understand the morphometrical, meristical characteristics and growth patterns of S. turturella from the Dompak Island was conducted in June-July 2018. The number of snail sampled was 400, with 46.98-83.07 TL mm and 13-46 grams BW. There were six morphological characteristics measured, there were total length, shell length, aperture length, shell width, shell depth and lip thickness, and there was one meristical characteristic count, namely the number of spire. Results shown that there are 5 morphometrical characteristic differences in males and females. Total length of male is longer than that of the female. While other characteristics, such as the shell length and aperture of the females were longer, the shell was wider, deeper and the lip was thicker than those of the males. The number of spire was 4-9 in males and 4-8 in females. The lengh-weight relationship shown that the growth of males and females is allometric negative (b=0.503).